Comic Life: An Effective Intervention to Reduce Aggressive Behavior in Early Childhood - Nasution, Mawaddah; Masitah, Widya; Naimi, Nadlrah; Sitepu, Juli Maini (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This study evaluates the effectiveness of the Comic Life intervention in reducing aggressive behavior among early childhood students. Utilizing an experimental design with pre-test and post-test control groups, the research was conducted over four weeks at RA As-Syafiiyah. Initial assessments identified potential issues through observations and interviews. Comic Life, an educational medium, was then developed and validated by experts. During the intervention phase, 21 children from class B engaged with Comic Life media through interactive storytelling sessions. Pre- and post-intervention data on aggressive behavior were collected using a validated questionnaire tailored to early childhood social-emotional development. The data were analyzed using the Wilcoxon signed-rank test and Mann-Whitney U test. Results indicate a significant reduction in aggressive behaviors post-intervention, with a large effect size (p = 0.003) and a rank-biserial correlation of -0.76. The findings underscore the potential of comic-based educational media in promoting positive behavioral outcomes among young children. This study highlights the importance of innovative and engaging methods in behavioral interventions, offering valuable insights for educators and policymakers. Future research should explore long-term effects and broader applications of similar interventions in different cultural and educational contexts to further validate these findings. Expanding the scope to include a range of behavioral issues and exploring the role of various types of educational media could provide a more comprehensive understanding of effective strategies for early childhood education.